The influence of the basil on colour, odour and taste of frankfurters. (September 2019) - Karan, D; Lukic, M; Djordjevic, V; Parunovic, N; Babic Milijasevic, J; Jovanovic, J; Nikolic, A
Abstract: Plants from the moderate climate zone are rarely used as seasoning in pasteurised sausages. Seasoning plants of the family Lamiaceae belong to this group (marjoram, basil, savory, sage, thyme). One of the reasons these herbs are rarely used to season meat products is the presence of the plant pigment, chlorophyll that can have undesirable influence on colour, odour and taste of meat products. The aim of this paper was to assess the influence of basil on colour, odour and taste of vacuum-packed frankfurters during 28 days of storage. Powdered, dried basil (0.1%, 0.3% and 0.5%) was added to frankfurters while control frankfurters were produced without herbs or spices. Assessment of colour, odour and taste acceptability of the frankfurters was performed by a panel of five assessors using a quantitative descriptive test, and the results of the ranking test were analysed statistically. When used at the level of 0.1% in the sausages, basil did not have negative influence on frankfurter colour, while larger quantities 0.3% and 0.5% adversely affected frankfurter colour. Basil in the smaller amounts of 0.1% and 0.3% stimulated development of a pleasant odour and taste in the frankfurters, while 0.5% basil had an undesirable effect on these sensory attributes.